Analisis beban kerja mental operator produksi aksesoris motor menggunakan metode National Aeronautics And Space Administartion Task Load Index (NASA TLX) di CV. Anugerah Teknik - Hanifah, Abu; Parnigotan, Sepriandi; Pangastuti, Nova (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
CV Anugerah Teknik is a company engaged in motorcycle components and accessories. Product development and certification can affect the workload of production operators. Therefore, it is necessary to analyze the mental workload of production operators. Data was collected through interviews and distributing questionnaires to production operators. This research uses the NASA-TLX method. The results of the analysis show that the average value of mental workload of production operators is 72.13, which falls into the high category. To reduce the workload, it is recommended to increase the number of operators in the production division, which can lower the score to 49.18.